Elaboración y uso de abonos orgánicos en la Comunidad de Imbabuela Bajo, Cantón Otavalo, Provincia de Imbabura, 2017 - Guerrero Aguilar, Ana Luisa (2018)
SUMMARY The present study aims determine the use and elaboration of the organic fertilizer in the Community of Imbabuela Bajo, for which we apply 20 interviews semi – structured to the producers members to the Community of Imbabuela Bajo to get main information, this information helped become making the training program go to impart to the producers. The results determine that the 95% of the farmers don’t know about the elaboration and use of the organic fertilizers, and only the 5% know about the elaboration and use these. Exist the interest in learn to make this fertilizers. This organic fertilizers are focused on improving agricultural production in this zone, because this presents benefits to the crop, besides their production costs are low. However the farmers of the community don’t received the sufficient information about this themes, this is the main cause that has limited their development and use. We conducted surveys about the use of organic fertilizers to diagnose the lack of knowledge regarding fertilizers. In conclusion the study determine the lack of knowledge from the farmers in the elaboration and use of the organics fertilizers, therefore it presents a limiting factor of its use and appliance in the crops, although they possess enough material of animals and vegetables for its converting process and to use in their zone.